Influence of electrode assembly on catalytic activation and deactivation of a Pt film immobilized H+ conducting solid electrolyte in electrocatalytic reduction reactions. Issue 13 (14th February 2015) - Hasnat, Mohammad A.; Islam, Muhammad Amirul; Rashed, M. A.
<x xml:space="preserve">Abstract</x> Symmetric assembly deactivated the electrocatalytic nitrate reduction process due to oxidation of copper atoms on the anode surface. In case of assymetric assembly, H2 evolution eroded copper oxides causing catalytic activation.